First Amendment Studies in Arkansas : The Richard S. Arnold Prize Essays - Smith, Stephen A., 1949- (Book collections on Project MUSE., 2016)
"This collection of fourteen essays written by young communication scholars at the University of Arkansas presents unique insights into how First Amendment issues have played out in the state. Rather than exploring the particular legal issues and the constitutional principles enunciated by the courts, First Amendment Studies tells the stories of actual people expressing challenged or unpopular points of view and reveals the ways that constitutional controversies arise from the actions of local officials and individual citizens. Drawing on public documents as well as extensive interviews with participants, these essays demonstrate the dynamics of democratic dissent--on college campuses, in public schools, in churches, on the streets, in the forests and on the farms, and in legislative chambers and courtrooms. Each essay was selected for the Richard S. Arnold Prize in First Amendment Studies, an endowed fund established in 1999 to encourage University of Arkansas graduate students in communication and the liberal arts to explore and examine questions about freedom of speech and freedom of religion."--Publlisher's website.